Practical UX design : a foundational yet practical approach to UX that delivers more creative, collaborative, holistic, and mature design solutions, regardless of your background or experience /: a foundational yet practical approach to UX that delivers more creative, collaborative, holistic, and mature design solutions, regardless of your background or experience. (2016) - Faranello, Scott
No abstract available